Linkage Guided Sequence Analysis Revealed a Novel Gene PKD1L2 for Adiponectin: The Long Life Family Study (LLFS). (17th December 2021) - Lee, Joseph; Anema, Jason; Wang, Lihua; Daw, Warwick; Christensen, Kaare; Zmuda, Joseph; Province, Michael; An, Ping
Abstract: Adiponectin is involved in regulating insulin resistance (IR) and is a potential regulator of healthy aging and lifespan. To identify novel variants associated with adiponectin, we further assessed our previously identified linkage peak on 16q23.2 (LODs=3.8). We used sequence data of 632 participants (age, 24-110 years) from 47 families of European ancestry in the Long Life Family Study, a study with familial clustering of exceptional longevity in the US and Denmark. Adiponectin levels were log-transformed, and adjusted for age, sex, sites, and PCs for ancestry. We found a variant in the PKD1L2 (rs527459046, p=2e-8, MAF=3%, r2=1.5%, accounting for linkage=28%). The PKD1L2, 1.4 Mb upstream of the CDH13 (adiponectin receptor gene) is expressed in heart, liver, and adipocytes, known to function as an ion-channel regulator or a GPCR regulator for aging-related lipolysis, IR, and adiponectin/leptin secretion. Haplotyping, epistatic and bioinformatic analyses will be engaged to capture additional/functional variants and regulatory networks.